2019
DOI: 10.1371/journal.pone.0224656
|View full text |Cite
|
Sign up to set email alerts
|

16S rDNA droplet digital PCR for monitoring bacterial DNAemia in bloodstream infections

Abstract: Repeated quantitative measurement of bacterial DNA on whole blood has been shown to be a promising method for monitoring bloodstream infection (BSI) with selected bacterial species. To enable broad use of this method, we developed a quantitative droplet digital PCR (ddPCR) method for 16S rDNA. It was validated with species-specific ddPCRs for Staphylococcus aureus (nuc), Streptococcus pneumoniae (lytA), and Escherichia coli (uidA) on spiked whole blood samples and on repeated whole blood samples (days 0, 1–2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 40 publications
2
17
0
Order By: Relevance
“…However, although this represents a limit for culture methods and for molecular methods based on RT-qPcR, here we demonstrated that ddPcR is not affected by the presence of fragmented dNA or cell debris thanks to the nanopartitions of gene targets and the dilutions of contaminants into thousands of droplets. In this context, other studies support our findings and the use of ddPcR for the detection of bacterial dNAemia during infection or for the monitoring of bacterial load in contaminated samples with PcR inhibitors (27,28).…”
Section: Rt-qpcr Ddpcr ----------------------------------------------supporting
confidence: 87%
“…However, although this represents a limit for culture methods and for molecular methods based on RT-qPcR, here we demonstrated that ddPcR is not affected by the presence of fragmented dNA or cell debris thanks to the nanopartitions of gene targets and the dilutions of contaminants into thousands of droplets. In this context, other studies support our findings and the use of ddPcR for the detection of bacterial dNAemia during infection or for the monitoring of bacterial load in contaminated samples with PcR inhibitors (27,28).…”
Section: Rt-qpcr Ddpcr ----------------------------------------------supporting
confidence: 87%
“…In the present study, we applied ddPCR to DNAs from single bacterial strains, bacterial mocks and metagenomic samples, demonstrating that it allows accurate absolute quantification of 16S rRNA gene copy numbers. Moreover, using DNA templates with different integrity levels, we demonstrated that 16S copy number quantification is strongly affected by DNA quality, a relevant issue that has not been addressed in previous studies [16, 20, 21, 29, 30]. Remarkably, we determined a precise correlation between quantification underestimation and DNA degradation levels, measured as DIN values, and demonstrated that a correction of the DNA mass, based on the underestimation value, allows one to estimate the 16S copy number accurately even in the most degraded metagenomic DNAs.…”
Section: Introductionmentioning
confidence: 58%
“…In the present study, we present data showing that ddPCR provides accurate quantification of 16S rDNA copy number in metagenomic DNAs. ddPCR is characterized by precise quantification, higher reproducibility compared to qPCR and higher sensitivity in low-copy-number detection [14, 20, 47]. Furthermore, ddPCR mitigates the effects of the presence of PCR inhibitors that may affect PCR sensitivity in 16S metabarcoding sequencing analysis [27, 48].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations